Allopregnanolone and its antagonist modulate neuroinflammation and neurological impairment - Bäckström, Torbjörn; Doverskog, Magnus; Blackburn, Thomas P.; Scharschmidt, Bruce F.; Felipo, Vicente (Neuroscience and biobehavioral reviews, 2024)
Neuroinflammation accompanies several brain disorders, either as a secondary consequence or as a primary cause and may contribute importantly to disease pathogenesis. Neurosteroids which act as Positive Steroid Allosteric GABA-A receptor Modulators (Steroid-PAM) appear to modulate neuroinflammation and their levels in the brain may vary because of increased or decreased local production or import from the systemic circulation. The increased synthesis of steroid-PAMs is possibly due to increased expression of the mitochondrial cholesterol transporting protein (TSPO) in neuroinflammatory tissue, and reduced production may be due to changes in the enzymatic activity. Microglia and astrocytes play an important role in neuroinflammation, and their production of inflammatory mediators can be both activated and inhibited by steroid-PAMs and GABA. What is surprising is the finding that both allopregnanolone, a steroid-PAM, and golexanolone, a novel GABA-A receptor modulating steroid antagonist (GAMSA), can inhibit microglia and astrocyte activation and normalize their function. This review focuses on the role of steroid-PAMs in neuroinflammation and their importance in new therapeutic approaches to CNS and liver disease. •Positive steroid Allosteric GABAA Modulators and antagonists influences neuroinflammation.•Local steroid-PAM concentrations are enhanced by increased expression of Transporter protein TSPO.•Steroid-PAM and a GABA-A receptor modulating steroid antagonist golexanolone dampens neuroinflammation.